Northeast municipal economic dynamics and the democratic context: an analysis based on the Bolsa Família program and the electoral market - Gledson e Silva, William; Danilo da Silva Ferreira, Francisco (Seven Editora, 2023)
This article aimed to analyze the behavior of the northeastern municipal economic dynamics explained in the Gross Domestic Product (GDP) with the volume of the Bolsa Família Program (PBF) destined to each entity, the proportion obtained from the Votes by the Elected Mayor (VPE) in front of of the set of voters participating in the local election and the Party Coalition of the Mayor-Elect (CPPE) established or not with the state governor, based on per capita variables, in 2004, 2008, 2012 and 2016. Methodologically, the measurement of research results in the quantile regression model for panel data. The results showed that the GDP responded positively to the PBF and negatively in most municipalities to the VPE and the CPPE did not bring favorable impacts on the northeastern municipal economy.DOI: https://doi.org/10.56238/devopinterscie-185